DEVELOPMENT OF THE DATA TRANSFERING SYSTEM USING SOC - Raisa Malcheva; Hazim Naaem (European Scientific Journal, ESJ, 2014)
In this article the systems on a chip is analyzed. Advantages of implementation of such systems on FPGA are described. Design of data transfering system is considered. Results of HDL simulation of developed system are shown.